Red de datos y su incidencia en la gestión académica de los institutos de nivel superior del cantón Babahoyo, año 2014.- Propuesta alternativa. - Guerrero Goyes, Kenya Anmarit (2015)
The development of this work highlights the importance of technology transfer from the point of view of a national competitiveness strategy, through these institutes can form a network with common interests, strengthening efforts, creating opportunities for academic and institutional cooperation and expanding the results of our progress of inclusive and equitable manner. Research in science and technology should be to achieve cross multiplicity and heterogeneity in their fields of action and the diversity of application in all areas involving social and productive development that each field used by implementing various methodologies, goals, agents, media, settings, and instruments, confirming the variety of approach that can be set through various factors, including: the social, political, economic, cultural, ethical needs, education, health, the environment, etc. . Considering all the previous statements, the present research analyzes the relevance of designing a virtual private LAN service in the Higher Institutes of the city of Babahoyo, in order to improve the processes of coordination between the institutes of the city. Finally, this research paper aims to contribute to achieving the objectives of the subject, based on two fundamental aspects: the dynamism of the institutes in its operations and procedures, establish technology transfer activities, including, human capital and strategic elements of operation and funding, secondly, through the approach of a number of recommendations and conditions of policies and performance in terms of technology transfer that already exist in our country.